Completeness criteria and filling of medical records in dental clinic of Cianjur General Hospital (January - April 2011) - Rosalina, Annisa; Suryanti, Netty; Wardani, Riana (Universitas Padjadjaran, 2012)
Introduction: The medical record documentation of patient treatment Provides the which in turn, must be maintained Clearly, concisely, comprehensively and accurately. Medical record and its filling criteria must be based on the regulation of the Minister of Health of The Republic of Indonesia No. 269/Menkes/Per/III / 2008 regarding to the medical record. The research was Aimed to unveil the completeness of both criteria and filling on medical records at the General Hospital’s Dental Polyclinic of Cianjur District. Methods: Survey-based descriptive method was applied within the research. Its Data was acquired through the examination on medical records and interviews. Random sampling was conducted to run the sampling technique. 89 pieces of outpatient’s medical records were embodied as samples. Results: Based on the research results, it is discovered that 6 out of 12 criteria (50%) are not listed within the medical record. Thus, the filling on medical records of 100% is found incomplete. Conclusion: Medical records Dental Clinic Regional General Hospital Cianjur according to standards Permenkes No. 269/2008 not inlude on complete criteria according to standards Permenkes No. 269/2008.